1986
DOI: 10.1007/bf00174065
|View full text |Cite
|
Sign up to set email alerts
|

Lithium decreases 5-HT1A and 5-HT2 receptor and ?2-adrenoreceptor mediated function in mice

Abstract: Lithium administration (LiC1, 10 mmol/kg, SC on day 1, followed by 3 mmol/kg twice daily subsequently) for 14 days to mice produced attenuation of the hypothermic response to injection of 8-hydroxy-2-(di-n-propylamino)tetralin (8-OH-DPAT, 0.5 mg/kg SC). Head twitch responses to the 5-HT-receptor agonist 5-methoxy-N,N-dimethyltryptamine (2.5 mg/kg IP) and to precursor loading with carbidopa (25 mg/kg, IP) and 5-hydroxytryptophan (100 mg/kg IP) were similarly attenuated. By contrast with this reduction of 5-hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

1986
1986
2006
2006

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 23 publications
3
22
1
Order By: Relevance
“…Nevertheless the data on the similarities between lithium and Ca2" antagonists on 5-HT function do provide a possible basis for an explanation as to why Ca2+ antagonists act similarly to antidepressants in various antidepressant screening tests (Mogilnicka et al, 1987;Geoffroy et al, 1988;Czyrak et al, 1989). It is also worth noting that lithium administration results in an attenuation of clonidine-induced hypoactivity (Goodwin et al, 1986a), an effect also produced by the Ca2+ antagonist drugs (Czyrak et al, 1989). Given these similarities between lithium and Ca2+ antagonists it is possible that the effects of Ca2+ antagonists on 5-HT function are through changes in ionic flux and disposition in the CNS.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Nevertheless the data on the similarities between lithium and Ca2" antagonists on 5-HT function do provide a possible basis for an explanation as to why Ca2+ antagonists act similarly to antidepressants in various antidepressant screening tests (Mogilnicka et al, 1987;Geoffroy et al, 1988;Czyrak et al, 1989). It is also worth noting that lithium administration results in an attenuation of clonidine-induced hypoactivity (Goodwin et al, 1986a), an effect also produced by the Ca2+ antagonist drugs (Czyrak et al, 1989). Given these similarities between lithium and Ca2+ antagonists it is possible that the effects of Ca2+ antagonists on 5-HT function are through changes in ionic flux and disposition in the CNS.…”
Section: Discussionmentioning
confidence: 95%
“…Administration of tranylcypromine to lithium pretreated rats results in the appearance of the complete 5-HT-mediated behavioural syndrome and an enhancement of the tranylcypromine/L-tryptophan-induced syndrome (Grahame-Smith & Green, 1974). Furthermore, lithium administration to mice leads to an inhibition of headtwitch behaviour (Goodwin et al, 1986a). The major contrasting action is that repeated lithium administration leads to an enhancement of 8-OH-DPAT-induced behaviour in the rat (Goodwin et al, 1986b) whereas felodipine administration acutely or for 3 days did not alter this response.…”
Section: Discussionmentioning
confidence: 99%
“…at least on the hippocampus [21,22], whereas 5-HT locally applied to the lateral septal nucleus produces suppression of firing [23], However, CMI pro duced a significant increase in the firing rate in lateral sep tal neurons and enhanced the effects of stimulating the dorsal raphe nucleus. CMI injected systemically produces a blockage of 5-HT uptake in vivo [10] and increases 5-HT levels, mainly in the raphe nuclei [8], a place rich in 5-HT1A receptors [14], the activation of which diminishes 5-HT release [24], An excess of 5-HT in the synaptic cleft produces a decrease in activity of the enzyme tryptophan hydroxylase [25] and in the release of 5-HT [26], In fact. CMI prevents the increase in 5-HT in rats submitted to chronic stress [27], Several 5-HT 1A agonists exert antide pressant actions [28][29][30], but at least their effects on lateral septal nuclei seem to reflect a disinhibitory process by simultaneous actions on 5-HT receptors [31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although other systems are also relevant (Banerjee et al, 1977;Koch et al, 2002;Newton et al, 2004;Tiraboschi et al, 2004), some evidence suggests that a component of the delay in response to ADT could be attributable to the time dependent desensitization of 5-HT1A receptors. Serotonin 1A-mediated responses in animals (Goodwin et al, 1986(Goodwin et al, , 1987cGreen, 1987Green, , 1988Hensler et al, 1991;Le Poul et al, 1997;Li et al, 1994;Martin et al, 1992;Mizuta and Segawa, 1988;Sleight et al, 1988), and in humans (Lesch et al, 1990;Rausch et al, 1990) have been shown to undergo adaptive changes with chronic ADT that are not seen with acute ADT. However, no one has explored whether adaptation in 5-HT1A receptor-mediated responses could account for lack of therapeutic effect to a given antidepressant.…”
Section: Introductionmentioning
confidence: 99%